Mr - FU, JIAHUI (2008)
China has become one of the most popular foreign direct investment (FDI) destinations since 1980s, and its automotive industry always an attractive playing field for the global automakers. As there was a gap in the passenger car market in before the 1980s, all the domestic manufacturers mainly at that time only produced trucks and buses for transportation, tractors for agriculture, and jeeps for military. Thus, the entry seems very necessary to supply this gap in the market; the early entry will help them to win the first move advantage. For European and U.S. automakers, the entry into China has become part of their global strategy. They strive to build up a business base in the Far East that will limit the dominance of Japanese firms. From a global strategy point of view, the step of entry into China seems very necessary; however, Chinas unstable institutional environment and different kinds of regulation limit the speed of entry. What the Chinese government wants to achieve through publishing the regulations to foreign funds, is to foster its own automotive industry and is not interested in turning China into an expansion base for European, American and Japanese auto industries. Simply, the government does not want to lose the control on this pillar industry while it opens to the world. Till the mid-1990s, the auto industry was still highly protected in China; high tariff and non-tariff trade barriers, screening, foreign equity limits and local content requirements are several common obstacles to the entry of foreigners. In the past, many researchers have studied the policies in Chinas automotive industry, but most of them mainly focus on two questions: 6 how does the protection environment in the auto industry affect the utility of domestic consumer by limiting their access to the cheaper import car?; and, how does the protected environment limit the development of the industry? Most of articles argued that the policy environment in China provides too much protection and is not good for the growth of domestic manufacturers. However, there are few studies focused on the foreign perspective; this paper would change the angle from the domestic side to foreign side. This paper looks to explore the link between policy regulations and entry model selection. In order to analyse this link, two famous joint ventures in the China automotive industry has been selected for study, the Shanghai Volkswagen and Guangzhou Peugeot. In the case, three dimensions about the entry strategy of these two companies will be analyzed. Finally, this paper is going to answer the question of whether the regulation is the main factor affect foreigners entry model selection and whether the limited availability of the entry model would be the important factor that affects the performance of joint ventures. In this paper, there are four main sections: Literature review, Methodology, Research analysis, and Conclusion. In the literature review section (Chapter 2), all the related theories and models about the entry model selection and entry strategies will be presented. The methodology (Chapter 3) will explain the research method of this research applied, the way to access the data, and the limitation of this research as well. Research analysis is a large section. All economic factors and regulations related to how foreign funds get in Chinas automotive industry will be analyzed in Chapter 4. The case studies of Shanghai Volkswagen and Guangzhou Peugeot will be shown in Chapter 5 and Chapter 6 respectively; the three dimensions of entry strategy of each joint venture: partner selection, control over alliance, 7 and conflict management will be fully analyzed here. Finally, this paper is going to present some implications through the comparison of Shanghai Volkswagen and Guangzhou Peugeot cases, and end with a conclusion: Regulation and Policy, in some degree, limit the number of available entry model choices to the foreigner, but any limitation on the entry model selection should not fully be responsible to the performance of the foreign funds in this industry. By implementing and designing a right entry strategy based on the assumption of limit entry model choice, the foreign funds can still perform very well.